Induction of plant defenses: the added value of zoophytophagous predators - Pérez-Hedo, Mertixell; Bouagga, Sarra; Zhang, Nina Xiaoning; Moerkens, Rob; Messelink, Gerben; Jaques, Josep A.; Flors, Victor; Broufas, George; Urbaneja, Alberto; Pappas, Maria L. (Springer, 2022)
Several biological control agents of the hemipteran insect families Miridae, Anthocoridae and Pentatomidae, as well as mites of the family Phytoseiidae are known as zoophytophagous predators, a subset of omnivores, which are primarily predaceous but also feed on plants. It has been recently demonstrated that zoophytophagous predators are capable of inducing defenses in plants through their phytophagy. Despite the vast fundamental knowledge on plant defense mechanisms in response to herbivores, our understanding of defense induction by zoophytophagous predators and applied implications is relatively poor. In this review, we present the physiological basis of the defense mechanisms that these predators activate in plants. Current knowledge on zoophytophagous predator-induced plant defenses is summarized by groups and species for the predators of economic importance. Within each group, feeding habits and the effects of their induced-plant defenses on pests and natural enemies are detailed. Also, the ecological implications of how the induction of defenses mediated by zoophytophagous predators can interact with other plant interactors such as beneficial soil microorganisms and plant viruses are addressed. Based on the above, we propose three approaches to exploit zoophytophagous predator-induced defenses in crop protection and to guide future research. These include using predators as vaccination agents, employing biotechnological approaches, as well as applying elicitors to elicit/mimic predator-induced defenses.